2016
DOI: 10.1016/j.kjms.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of switching therapy of luteinizing hormone–releasing hormone analogue for advanced prostate cancer

Abstract: This study was conducted to determine the efficacy of switching therapy with a second-line luteinizing hormone-releasing hormone (LHRH) analogue after prostate-specific antigen (PSA) progression for advanced prostate cancer. We enrolled 200 patients, from December 2005 to September 2013, with nodal positive, metastatic prostate cancer or disease progression after definite treatment receiving continuous LHRH analogue therapy with monthly depot leuprorelin(sc) acetate 3.75 mg/vial (LA) or goserelin acetate(sc) 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Additionally, Van Coppenolle et al (8) demonstrated that T levels are higher in controls compared with animals treated with sulpiride, which is not congruent with the aforementioned results. Previous studies have indicated that an increase in PRL inhibits gonadotrop-releasing hormone (GnRH) release from the hypothalamus and reduces LH release via a negative feedback regulatory mechanism (54,55). The structure and function of the prostate are influenced by the hypothalamus-pituitary-gonadal axis (56), while tissue growth and hormone secretion are primarily affected by T regulation (57).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Van Coppenolle et al (8) demonstrated that T levels are higher in controls compared with animals treated with sulpiride, which is not congruent with the aforementioned results. Previous studies have indicated that an increase in PRL inhibits gonadotrop-releasing hormone (GnRH) release from the hypothalamus and reduces LH release via a negative feedback regulatory mechanism (54,55). The structure and function of the prostate are influenced by the hypothalamus-pituitary-gonadal axis (56), while tissue growth and hormone secretion are primarily affected by T regulation (57).…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer is a male malignant tumor and its incidence is the highest among all male malignant tumors (11). It has been reported that its incidence in male tumors is 9.7% (12,13). The cause of prostate cancer currently remains unclear (14).…”
Section: Discussionmentioning
confidence: 99%